Functional mechanism and clinical implications of MicroRNA‐423 in human cancers - Ke, RuiSheng (Cancer Med, 2020)
MicroRNAs play a vital role in the regulatory mechanisms of tumorigenesis. Current research indicates that microRNA‐423 (miR‐423) is abnormally expressed in various human tumors and participates in multiple signaling pathways of cancer progression. In most studies, miR‐423 was confirmed as oncomiR, while a few contradictory reports considered miR‐423 as an anticancer miRNA. The paradoxical role in cancer may hinder the application of miR‐423 as a diagnostic and therapeutic target. Simultaneously, the interaction mechanism between miR‐423 and lncRNA also needs attention. In this review, we have summarized the dual role of aberrant miR‐423 expression and its mechanisms in tumorigenesis, and the therapeutic potential of miR‐423 in human tumors.